A comparative study of use of polypropylene and composite mesh in inguinal hernia repair - Singh, Amandeep; Khichy, Sudhir; Sinha, Shourabh; Singh, Sonam; Kaur, Haramritpal; Singh, Jaskaran; Kumar, Sunil (International Surgery Journal, 2022)
Background: Hernia most probably has been a disease ever since mankind existed. Repair of inguinal hernia is one of the commonest surgical procedures worldwide. Currently, about one million meshes are used per year world-wide for hernia repair. Therefore, surgical repair of hernia is a hot area of research for keeping the recurrence rates low with few complications using an ideal mesh material. The aim of the study was to compare the use of Polypropylene mesh and Composite mesh in patients undergoing inguinal hernia repair. Methods: A total of 60 patients of either gender were enrolled in the study and followed upto8 weeks. Out of 60, 30 patients were offered Polypropylene mesh hernioplasty and in rest 30 patients Lichtenstein hernioplasty with composite mesh was done. Postoperative analysis was made in terms of postoperative pain, complications and recurrence. Results: Both the groups were comparable in terms of age and gender. Post-operative pain at 24 hours was considerably lower in patients undergoing hernia repair using Composite mesh than with Polypropylene mesh group. However, most of the post-operative complications were comparable in early post-operative period and on subsequent follow up visits in both groups. Conclusions: Polypropylene mesh and composite mesh were comparable in terms of ease of mesh placement and post-operative complications in patients of inguinal hernia repair.